Moisture-Dependent Physical Properties of Onion (Allium cepa L.) Seed - Yalcin, I.; Cetin, M.; Ozarslan, C. (Asian Journal of Chemistry, 2010)
The physical properties of onion seed were determined as a function of moisture content in the range of 7.81 to 23.99 % dry basis. The average length, width and thickness were 2.98, 1.97 and 1.41 mm, at a moisture content of 7.81 % dry basis, respectively. In the moisture range from 7.81 to 23.99 % dry basis, studied the rewetted onion seed showed increase in the thousand seed mass from 3.85 to 4.33 g, the projected area from 2.27 to 3.43 mm2, the sphericity from 0.680 to 0.688, the porosity from 49.82 to 51.85 % and the terminal velocity from 4.80 to 5.23 m s-1. The bulk density decreased from 550.18 to 521.68 kg m-3 and the true density from 1096.49 to 1083.46 kg m-3 with an increase in the moisture content range of 7.81-23.99 % dry basis. The static coefficient of friction of onion seed increased linearly against the surfaces, namely, rubber (0.227 to 0.309), aluminium (0.159 to 0.228), stainless steel (0.149 to 0.195) and galvanized iron (0.189 to 0.244) as the moisture content increased from 7.81-23.99 % dry basis.